2011
DOI: 10.1124/jpet.111.179978
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticles Inhibits Oxidative Stress and Nuclear Factor-κB Activation in H9c2 Cardiomyocytes Exposed to Cigarette Smoke Extract

Abstract: Cigarette smoke contains and generates a large amount of reactive oxygen species (ROS) that affect normal cellular function and have pathogenic consequences in the cardiovascular system. Increased oxidative stress and inflammation are considered to be an important mechanism of cardiovascular injury induced by cigarette smoke. Antioxidants may serve as effective therapeutic agents against smoke-related cardiovascular disease. Because of the presence of oxygen vacancies on its surface and self-regenerative cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(115 citation statements)
references
References 35 publications
9
105
0
1
Order By: Relevance
“…Similar findings were observed in mice exposed to WPS for 1 month [14]. In cultured rat H9c2 cardiomyocytes, CS extract was found to cause upregulation of NF-κB-regulated inflammatory genes TNFα, IL-6 and IL-1β and to induce depletion of antioxidant enzymes [37]. It remains to determine if there is any selectivity of WPS components to specific heart compartments leading to a differential proinflammatory and procoagulatory effects.…”
Section: Discussionsupporting
confidence: 52%
“…Similar findings were observed in mice exposed to WPS for 1 month [14]. In cultured rat H9c2 cardiomyocytes, CS extract was found to cause upregulation of NF-κB-regulated inflammatory genes TNFα, IL-6 and IL-1β and to induce depletion of antioxidant enzymes [37]. It remains to determine if there is any selectivity of WPS components to specific heart compartments leading to a differential proinflammatory and procoagulatory effects.…”
Section: Discussionsupporting
confidence: 52%
“…23 Moreover, CeO 2 nanoparticles have been reported to reduce oxidative signaling and cell death induced by cigarette smoke, diesel exhaust, and hydrogen peroxide. [24][25][26] In contrast, other in vitro and in vivo experiments suggest that CeO 2 nanoparticles produce inflammation, reactive oxygen species, lipid peroxidation, liver and lung damage, acute and chronic fibrotic effects, and altered macrophage phenotypes. [27][28][29][30][31] Variation in target species/ cell type, experimental design (exposure concentration and duration) and nanoparticle characteristics (shape, size, purity, Figure 1, stained with propidium iodide and analyzed using flow cytometry.…”
Section: Discussionmentioning
confidence: 91%
“…[20] This leads to the protection of eukaryotic cells against oxidative stress, as it was previously reported in many studies. [21,22] Niu et al [23] and Korsvik et al [24] have proposed a mechanism, shown in Equations (2) and (3), by which ceria can scavenge radicals thanks to its redox potential.…”
Section: Protective Effects Of Ceria Materialsmentioning
confidence: 99%